I-106 Hepatitis viruses in HIV infection. (April 2018) - Sherman, Kenneth
Abstract : Viral hepatitis represents an important comorbidity among those with HIV infection. The epidemiology and pathophysiology is often altered compared to the general population with increased prevalence, increased risk of chronicity, alteration of viral setpoints, and more rapid progression of hepatic fibrosis in many co-infected individuals. Recently, outbreaks of hepatitis A among MSM with HIV have been reported. Hepatitis B infection is often unrecognized and represents an important contributor to morbidity through both liver failure and increased risk of hepatocellular carcinoma. Hepatitis C is also associated with higher rates of chronicity following acute infection, and rapid hepatic fibrosis leading to liver related death. Treatment of HCV is efficacious but must take into account the underlying antiretroviral regimen. Hepatitis D may be more frequent among HBV/HIV infected persons than has been previously recognized, and also represents an independent risk of HCC. Hepatitis E infection can lead to chronic infections in those with HIV and other immunosuppressed states. Standard vaccination practices that are highly effective in the general population to prevent hepatitis A and B are of lower utility among those with HIV and alternative vaccine strategies should be employed. Conclusion: Co-infection of hepatitis viruses with HIV leads to alterations in natural history, as well as prevention and treatment strategies. Care providers must be cognizant to these differences in order to provide optimal care for the HIV-infected patient.